Handbook of epigenetics the new molecular and medical genetics - Tollefsbol, Trygve O. (Academic Press, an imprint of Elsevier, 2017)
Epigenetics is considered by many to be the "new genetics" because of the overwhelming evidence of the contribution of non-genetic factors such as nutrition, environment, and chemical exposure on gene expression. The effects of epigenetics are vast, including tissue/organ regeneration, X-chromosome inactivation, and stem cell differentiation and genomic imprinting and aging. Aberrations of epigenetics influence many diseases for which clinical intervention is already in place, and many novel epigenetic therapies for cancer, immune disorders, neurological and metabolic disorders, and imprinting diseases are on the horizon. This comprehensive collection of reviews written by leaders in the field of epigenetics provides a broad view of this important and evolving topic. From molecular mechanisms and epigenetic technology to discoveries in human disease and clinical epigenetics, the nature and applications of the science will be presented for those with interests ranging from the fundamental basis of epigenetics to therapeutic interventions for epigenetic-based disorders.--Provided by publisher.